2018
DOI: 10.2217/bmm-2018-0123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiple Biomarkers for Mortality Prediction in Patients with Acute Heart Failure of Ischemic and Nonischemic Etiology

Abstract: Aim: To investigate the prognosis of soluble ST2 (sST2), galectin-3 and N-terminal pro-B-type natriuretic peptide (NT-proBNP) for death related to ischemic and nonischemic etiology of acute heart failure (HF). Methods: The associations between biomarkers and death were determined in 1020 patients admitted to hospital with acute HF. Results: During 1-year follow-up, 162 patients died. Multivariable regression analysis showed that the hazard ratios of sST2 and NT-proBNP for 1-year all-cause death was similar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…По другим данным качество модели прогноза на основе sST2 (по AUC) при ИМ было ниже, чем на основе NT-proBNP [10,12]. Однако в большинстве работ на эту тему значимость sST2 для прогноза неблагоприятных исходов ОСН не зависела от NT-proBNP и не снижалась при включении обоих биомаркеров в модель при увеличении ее точности [13,14], что явилось обоснованием концепции мультимаркерных систем стратификации риска, в т.ч. при ИМпST [8,12].…”
Section: Discussionunclassified
“…По другим данным качество модели прогноза на основе sST2 (по AUC) при ИМ было ниже, чем на основе NT-proBNP [10,12]. Однако в большинстве работ на эту тему значимость sST2 для прогноза неблагоприятных исходов ОСН не зависела от NT-proBNP и не снижалась при включении обоих биомаркеров в модель при увеличении ее точности [13,14], что явилось обоснованием концепции мультимаркерных систем стратификации риска, в т.ч. при ИМпST [8,12].…”
Section: Discussionunclassified
“…Eight studies [Clementy 2018;de Boer 2011;Carrasco-Sanchez 2013;Beltrami 2016;van Vark 2017;Lala 2018;Testa 2018;Zhang 2018] evaluated the relationship between galectin-3 and all-cause mortality of AHF, in which encountered 642 (22.0%) death out of 2915 AHF patients. Using the random-effects model, the result indicated that for every 1% increase in plasma galactosin-3, the associated risk of allcause mortality increased by 117% (HR 2.17, 95% CI 1.27-3.08, I 2 = 90.7%).…”
Section: Literature Searchmentioning
confidence: 99%
“…There is no strong evidence that single biomarker use is superior to a multiple biomarker strategy for every clinical condition in HF patients. For instance, the MOLI-TOR (Impact of Therapy Optimisation on the Level of Biomarkers in Patients with Acute and Decompensated Chronic Heart Failure) study has shown that serial measurements of multiple biomarkers (C-terminal fragment of pre-pro-vasopressin, NT-proBNP, midregional pro-atrial natriuretic peptide, mid-regional pro-adrenomedullin, and C-terminal pro-endothelin-1) in advanced HF were no better than measurements of the C-terminal fragment of pre-pro-vasopressin [157]. Pandey A. et al (2021) [158] evaluated the application of a biomarker-based risk score to identify patients with dysglycemia that were at high risk of incident HF.…”
Section: Multiple Biomarker Strategiesmentioning
confidence: 99%